(untitled) (Vietnam Journal of Community Medicine, 2026)
Objective: To describe selected toxicities of the XELOX regimen as adjuvant chemotherapy in elderly patients with gastric cancer at Vietnam National Cancer Hospital. Subjects and methods: A retrospective descriptive study was conducted on 70 patients aged ≥ 60 years with stage II-III gastric cancer who underwent radical surgery and received adjuvant XELOX chemotherapy at K Hospital from January 2022 to December 2024. Toxicities were graded according to the CTCAE version 5.0. Results: The most common hematologic toxicities were anemia, neutropenia, and thrombocytopenia, occurring in 58.5%, 55.7%, and 27.2% of patients, respectively; grade 3-4 neutropenia was observed in 8.6%. Non-hematologic laboratory toxicities were mainly mild elevations of GOT and GPT, reported in 27.1% and 30% of patients, respectively, with no grade 4 events. The most frequent clinical toxicities included anorexia 52.8%, peripheral neuropathy 45.8%, nausea 41.4%, hand-foot syndrome 37.1%, diarrhea 28.7%, and vomiting 21.4%; no grade 3-4 clinical toxicities were recorded. Grade 3-4 neutropenia tended to be more frequent in patients receiving full-dose treatment than in those receiving reduced-dose treatment, 18.7% versus 13.1%, OR = 1.54, and in patients aged ≥ 70 years compared with those aged 60-69 years, 30% versus 10.3%, OR = 3.71. Conclusion: Toxicities of adjuvant XELOX chemotherapy in elderly patients with gastric cancer were mainly mild to moderate. Grade 3-4 toxicities were uncommon and predominantly consisted of neutropenia. Close monitoring of hematologic toxicity is needed, especially in patients aged ≥ 70 years and those receiving full-dose treatment.